Self-care, balance and the IB learner profile - Allen, Matthew (2013)
Anecdotal evidence suggests that educators tend to expend themselves for their students with little thought for themselves, often leading to excessive stress, work-related illness, burnout, and attrition. The following discussion adapted from Self-Care for Teachers (Allen, 2013) reviews the international research on this topic and proposes an alternative approach. The research not only confirms this persistent pattern of excessive stress, overwork, and illness but also confirms educators’ typical inattention to their own needs. Conventional approaches to the problem of excessive stress, overwork and its attendant maladies focus on the external: management strategies such as induction and mentoring programs, salary incentives, or more recently, teacher help lines and wellness programs. The author advocates a more balanced approach, looking inward as well as outward for solutions to this perplexing problem. Although balance is often conceived as a static ideal of symmetry and proportion, it may be best understood–especially in an educational context– as the practical dynamic process of “moving artfully between extremes”, a definition which might equally apply to classroom management, curriculum design, assessment strategies, professional development, prevalent attitudes, and work-life rhythm.